Supporting change in chronic disease risk behaviours for people with a mental illness: a qualitative study of the experiences of family carers - Jacqueline M. Bailey; Vibeke Hansen; Paula M. Wye; John H. Wiggers; Kate M. Bartlem; Jennifer A. Bowman (BMC, 2018)
Abstract Background People with a mental illness experience greater chronic disease morbidity and mortality, and associated reduced life expectancy, compared to those without such an illness. A higher prevalence of chronic disease risk behaviours (inadequate nutrition, inadequate physical activity, tobacco smoking, and harmful alcohol consumption) is experienced by this population. Family carers have the potential to support change in such behaviours among those they care for with a mental illness. This study aimed to explore family carers': 1) experiences in addressing the chronic disease risk behaviours of their family members; 2) existing barriers to addressing such behaviours; and 3) perceptions of potential strategies to assist them to provide risk behaviour change support. Methods A qualitative study of four focus groups (n = 31), using a semi-structured interview schedule, was conducted with carers of people with a mental illness in New South Wales, Australia from January 2015 to February 2016. An inductive thematic analysis was employed to explore the experience of carers in addressing the chronic disease risk behaviours. Results Two main themes were identified in family carers' report of their experiences: firstly, that health behaviours were salient concerns for carers and that they were engaged in providing support, and secondly that they perceived a bidirectional relationship between health behaviours and mental well-being. Key barriers to addressing behaviours were: a need to attend to carers' own well-being; defensiveness on behalf of the family member; and not residing with their family member; with other behaviour-specific barriers also identified. Discussion around strategies which would assist carers in providing support for health risk behaviours identified a need for improved communication and collaboration between carers and health services accessed by their family members. Conclusions Additional support from general and mental health services accessed by family members is desired to assist carers to address the barriers to providing behaviour change support. Carers have the potential to support and extend health service interventions aimed at improving the chronic disease risk behaviours of people with a mental illness but may require additional information, and collaboration from services. Further research is needed to explore these constructs in a large representative sample.